The New Monroe Doctrine and the Retreat of European Empires After 1865 (Nuovi Autoritarismi e Democrazie: Diritto, Istituzioni, Società (NAD-DIS), 2025)
During the Civil War, Abraham Lincoln, William Seward, and the US diplomatic corps wrapped the emancipation policy in lofty political ideology. The Union, they told the world, was fighting to preserve republican principles, democratic freedom, equality, and opportunity for all. After the war, there were two Reconstructions, domestic and international. International Reconstruction sought to ensure that the Western Hemisphere would become safe for republicanism. Initially a warning against further European colonization of the Americas, after 1865 the Monroe Doctrine propagated the idea that the entire Western Hemisphere must be a haven for republicanism and that monarchy and slavery were no longer welcome.
Keywords: Lincoln, Abraham, 1809-1865; Seward, William, 1801-1872; The New Monroe Doctrine; United States; Europe